Widows and divorcees in later life : on their own again - Jenkins, Carol L. (Routledge, 2014)
Get a fresh perspective on how older women adapt to life without a spouse! Widows and Divorcees in Later Life: On Their Own Again examines new perspectives on the problems older women face adjusting to life without a spouse. The book examines the transition from the togetherness of marriage to the solitude of being suddenly single, exploring how older widows and divorcees adapt. A multidisciplinary panel of practitioners, researchers, and academics addresses the challenges facing elderly women after a divorce or the death of a spouse, including issues of physical and psychological well.